On Generalizations of the Hilbert Nullstellensatz for Infinity Dimensions (A Surwai) - Kravtsiv, V. (Journal of Vasyl Stefanyk Precarpathian National University, 2015)
The paper contains a proof of Hilbert Nullstellensatz for the polynomials on infinite-dimensional complex spaces and for a symmetric and a block-symmetric polynomials